Analisis Strategi Pemilihan Negara-Negara Tujuan Ekspansi Hulu Migas Studi Kasus pada PT Pertamina (Persero) - , Saptianta Aribawa Sabaris ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The condition of Indonesia's oil production continued to decline from year to year while consumption continues to rise. Ministry of Energy notes that Indonesia every day is planned to import oil and oil products up to 802 thousand barrels per day in 2012. While the condition of the gas fulfillment of Indonesia will be a deficit era in next two years if alternative production or import strategies are not immediate performed. Overall Indonesia faced a deficit condition of the oil and gas. In the upstream sector to meet the needs of oil and gas is actively looking for new oil and gas resources not only in domestic and furthermore through overseas expansion. Efforts have been conducted since 1990's and to date there are eight assets in seven countries belonging to Pertamina. Unfortunately almost all of the assets in exploration phase and still have not been able to contribute much to the Indonesian oil and gas needs. To continue to grow become World-Class oil and gas company Pertamina has set strategic themes âAggressive Upstream Profitable Downstreamâ where one of the programs is to expand upstream business in overseas in the production field or development field. This thesis tries to provide alternatives as the expansion target countries of oil and gas business throughout the world where there are 31 candidate countries as follows: United States, Canada, Mexico, Venezuela, Brazil, Ecuador, Peru, Argentina, Colombia, Bolivia, Russia, Kazakhstan, Norway , England, United Arab Emirates, Qatar, Oman, Syria, Yemen, Nigeria, Algeria, Egypt, Ghana, Mozambique, China, Australia, Malaysia, Vietnam, Papua New Guinea,Thailand, and Brunei.